The comparative study of intraperitoneal access by open versus close method to create pneumoperitoneum in laparoscopic surgeries - Parmar, Hiren D.; Vadher, Lalit (International Surgery Journal, 2023)
Background: Laparoscopy is a Latin word; ‘laparo’ means abdomen and ‘scopein’ means to examine, hence it is an art of examination of abdomen and visceral contents. laparoscopic procedure has been revolutionized and come under routine practice by surgical subspecialties because of it has many advantages over conventional laparotomy like small size scar, short hospital stays, less chance of wound infection, minimal postoperative pain, quick recovery after surgery. The aim of the study was to compare the rates and nature of complication during creation of pneumoperitoneum in open and closed laparoscopic procedure. Methods: This is a single centre, comparative, observational study. Tools of study include, observation, intraoperative and post-operative observation of complications. Nonprobability sampling (purposive sampling) technique was used in this study. Sample size was 44 (in each group). Written and Informed consent has been taken from all patients who were underwent abdominal laparoscopic surgery. Results: This study represents the comparison between different open and closed methods for creation of pneumoperitoneum in laparoscopic abdominal surgeries. In this study, according to classification of complication at entry level in open method omental injury found in 2 (12%) patients; extra peritoneal insufflations 1 (6%), port site gas leakage 10 (59%), loss of space 1 (6%), entry in wrong plane 3 (17%). In closed method omental injury found in 4 (13%) patients; extra peritoneal insufflations 4 (13%), port site gas leakage 8 (27%) loss of space 5 (17%), entry in wrong plane 7 (23%), abdominal wall haematoma 4 (13%). Conclusions: Open method is merely safer than closed technique but due to small number of patients took into study as well as study time period is short. Final judgment for the research, multi centric trials in different institutions are required for the initial, crucial, and technically challenging step of newly emerging field of surgery.